Automated displacement measurements on historical canvases - Fausto Del Sette (Heritage Science, 2017)
Abstract Background In this paper we describe a configurable system based on laser displacement sensors for the contactless acquisition of 3D and 2D shapes of near-planar objects such as the paintings. Methods The system is based on two single-point laser triangulation sensors, a planar robot and a suite of software for driving the sensors, acquiring and post-processing the collected data. As a demonstration of the developed system we monitored three artifacts with the different aims to monitor the elastic properties of the artworks and the effectiveness of support frames in compensating the micro-climate fluctuations: the “Annunciazione” Antonello da Messina, the “Paliotto di San Domenico”, and the “Portiera Oddi-Montesperelli”. Results In the “Annunciazione” case, the canvas response to tensioning trials was analyzed. The collected data permitted to quantify a maximum displacement of 0.9 and 1.5 mm for the tensioning tests at 1 and 2 mm, respectively. In the “Portiera” case, the displacement difference between the left and right canvas sides was (1.0 ± 0.13)%, due to the inherent anisotropy of the material and by the structure of the artifact. In the “Paliotto” case, instead, minor displacement variations of the gilt leather due to the environment were observed, due to the analysis conducted prior of the restoration. Conclusions The overall obtained results demonstrated that the system is able to provide useful data for the art conservation field, with a max inaccuracy less than 100 μm.